Identifikasi Kerusakan Tutup Radiator Terhadap Suhu Engine Toyota Kijang 5K - Wilarso Wilarso Arso; Firman Gunawan (Universitas Medan Area, 2020)
Lack of radiator water in the 5K Kijang car cooling system, has an impact on decreasing vehicle performance. This leakage causes the cooling water in the radiator to decrease and can trigger a high cooling system temperature (overheating) on the engine. The discussion of the effect of damage to the radiator cap on the engine temperature of the Toyota Kijang 5K is able to help improve the understanding of vehicle users in general about the cooling system, can treat and repair if there is damage to the radiator cap. The radiator cap test was carried out by observation on a 5K Toyota deer by testing the radiator cap pressure using a radiator cup tester and visualizing the radiator cap components. After inspection there is damage to the radiator cap seal and the results of the radiator cap test 0.6 kgf / cm2 which causes the radiator cap pressure to be low, while the standard pressure is 0.9 kgf / cm2 - 1.03 kgf / cm2 and there is damage to the radiator cap seal so that it can cause engine overheating. Repair steps by replacing the new radiator cap components, efforts that need to be considered to prevent losses due to damage to the cooling system components, check the level of coolant, do a daily check properly and correctly, do preventive maintenance regularly.